Ostre zapalenie nabłonka barwnikowego u 18-letniej pacjentk - Gotz-Więckowska, Anna; Bernardczyk-Meller, Jadwiga; Siwiec-Prościńska, Joanna; Kocięcki, Jarosław (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
We report case of acute retinal pigment epithelitis (ARPE), a very rare ophthalmic disorder, which has a very good final visual prognosis. The 18 years old woman was examined by ophthalmologist for sudden visual decrease of vision and dark spot in visual field of her left eye. The best corrected visual acuity (BCVA) of the left eye at the initial diagnosis was 0.1 and after 4 months improved to 0.9. The diagnosis or ARPE was made on the basis of fundoscopy, fluoresceine angiography, electroretinography and optical coherence tomography (OCT) examination.